THE ROLE OF PUBLIC RELATIONS MUHAMMADIYAH UNIVERSITY LAMPUNG IN INCREASING A POSITIVE IMAGE - Asniar, Immawati; Anggraini, Marina Ghanis (Journal of Public Relations and Digital Communication (JPRDC), 2023)
The educational institutions basically need Public Relations which aims to gain goodwill, trust, mutual understanding and a good image from the public. Increased competition among tertiary institutions makes each tertiary institution challenged to form a positive image to the public. Prospective students will have a special interest in campuses that have a positive image. The problem in this research is what is the role Public Relations Muhammadiyah University of Lampung in Improving Positive Image. The research methodology is a qualitative constructivism approach with the case study method which is carried out in its entirety, comprehensively and in depth using a variety of data sources. The results of the research show that there are four main roles required of a Public Relations namely, as Communicator, Public Relations Communicate intensively through media and community groups, Relations, Public Relations capabilities building positive relationships between institutions represented and internal and external public, backup management, carry out management support or support departmental activities other in tertiary institutions for the creation of common goals, good image makers, create positive college image and publicity.